A New Isoflavanol from the Fruits of Kotschya strigosa (Fabaceae). Issue 4 (April 2016) - Awouafack, Maurice D.; Tchuenguem, Roland T.; Ito, Takuya; Dzoyem, Jean P.; Tane, Pierre; Morita, Hiroyuki
Abstract : The phytochemical investigation of the MeOH extract from fruits of Kotschya strigosa using repeated normal and reversed‐phase column chromatography and Sephadex LH‐20 chromatography led to the isolation and characterization of a new isoflavanol, named kotstrigoisoflavanol (1 ), together with three known compounds, diosmetin (2 ), β ‐sitosterol (3 ), and the 3‐ O ‐ β ‐d‐glucopyranoside of β‐ sitosterol (4 ). The antioxidant activity of crude extract, 1, and2 was determined using the 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH˙) method. The crude extract ( IC 50 61.7 ± 0.2 μg/ml) and2 ( IC 50 70.2 ± 0.1 μg/ml) showed moderate antioxidant activities, while1 was weakly active ( IC 50 153.1 ± 0.1 μg/ml), as compared with the standard referencel ‐ascorbic acid ( IC 50 21.9 ± 0.0 μg/ml). Abstract :